Hubungan Riwayat Atopik dan Masa Kerja dengan Kejadian Dermatitis Kontak Iritan pada Pekerja Cuci Motor di Kecamatan Jebres Surakarta - Nur Ismi Mustika Febriani; Nurrachmat Mulianto; . Hardjono (Nexus Kedokteran Komunitas, 2013)
Background: Irritant contact dermatitis is the most common form of occupational skin disease, accounting for up to 80% of all occupational skin disorders. Atopic history and work period are risk factors for irritant contact dermatitis. This study aimed to analyze the relation of atopic history and work period with the incidence of irritant contact dermatitis on motorcycle wash workers at District of Jebres in Surakarta. Method: This study was observational analytics with cross sectional approach. Subjects were male who worked in motorcycle wash at District of Jebres in Surakarta. Samples were 60 workers. This samples were taken by fixed disease purposive sampling. Data were collected by questionaire and digital autograph, then analyzed by multiple logistic regression analysis using SPSS 17.0 for windows. Result: The results of atopic history analysis showed that there was a positive relationship between atopic history and the incidence of irritant contact dermatitis. Motorcycle wash workers who had atopic history would increase the risk to get irritant contact dermatitis 8.44 times than workers who hadnt atopic history (OR = 8.44; CI 95% 2.203 s/d 32.341). The results from analysis variable of work period showed significant relationship between work period and the incidence of irritant contact dermatitis. The worker who had worked ? 3 years had a greater risk 4.91 times than workers who had worked < 3 years (OR = 4.91; CI 95% 1.365 s/d 17.675). Conclusion : There was a positive relationship between atopic history and work period with the incidence of irritant contact dermatitis on motorcycle wash workers at District of Jebres in Surakarta. The motorcycle wash workers who had atopic history and had worked ? 3 years would increase the risk of irritant contact dermatitis. Keywords : irritant contact dermatitis, atopic history, work period, motorcycle wash workers